Ethnomathematics in the Calculation of Sasak Traditional Heritage: Identification of the Concepts of KPK and FPB in the Aul and Radd Mechanism - Miftahul Makwa; Salwatul Solehah; Eka Kurniawan; Muhammad Turmuzi (Balai Publikasi Indonesia, 2026)
This study aims to identify and analyze the mathematical concepts contained in the Sasak traditional heritage distribution system in Central Lombok through an ethnomathematical approach. The research uses a descriptive qualitative approach with a focused ethnography. The data was collected through a semi-structured interview with H. Nurul Mustofa as a Religious Stakeholder and Traditional Stakeholder in Penujak Village, West Praya District, Central Lombok Regency on April 12, 2026, as well as a documentation study of faraid books used by the resource persons. The results of the study found seven mathematical concepts that were actually applied: (1) the local numeracy system (sekek, due, three, four, lime) that corresponds to the concept of formal numbers; (2) tiered counting operations (addition, subtraction, division); (3) the concept of fractions with the local terms half/half, three, and four; (4) a 2:1 ratio between male and female heirs; (5) Smallest Commonwealth Multiples (KPK) which are implicitly applied in the aul mechanism when the total share exceeds 100% of the property; (6) Largest Federal Factor (FPB) in the radd mechanism when there is a proportionate return of residual property; and (7) the concept of measurement with are, sack, and hand span units. The inheritance distribution procedure is carried out through six systematic stages. The relationship of formal mathematics to customary practice is analyzed from three dimensions: conceptual correspondence, difference in representation, and pedagogical implications. The findings prove that the KPK and FPB work synergistically in one system, and this mathematical knowledge has great potential to be used as a context for meaningful mathematics learning in accordance with the spirit of the Independent Curriculum.